Analýza vybrané firmy - Zavoralová, Eva (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Diplomová práce je zaměřena na analýzu realitní společnosti M&M reality holding, a.s.. V rámci mapování společnosti se zaměřuji na rozbor oborového okolí pomocí PEST analýzy, Porterův model pěti konkurenčních sil, SWOT analýzu a finanční analýzu. V závěru práce navrhuji doporučení, která by měla vést ke zlepšení současné situace.

The master´s thesis is focused on the analysis of real estate company M&M reality holding, a.s.. The mapping of the analysis focuses on the professional environment using the PEST analysis, Porter's five forces analysis, SWOT analysis and financial analysis. In the conclusion I propose recommendations that should lead to improve the current situation.
Analysis of the Selected Firm
Keywords: PEST analýza; SWOT analýza; Porterův model pěti konkurenčních sil; Finanční analýza; PEST analysis; SWOT analysis; Porter's Five Forces analysis; Finanční analysis